Factors Affecting Performance and Recovery in Team Sports: A Multidimensional Perspective - Athos Trecroci; Damiano Formenti; Jason Moran; Dino Pedreschi; Alessio Rossi; Diego Brito de Souza; Roberto López-Del; R. Campo; Victor Resta; Juan Moreno-Perez; Dorsaf Sariati; Raouf Hammami; et al. (2022)
it is a pioneering approach to the world of academia, radically improving the way scholarly research is managed.The grand vision of Frontiers is a world where all people have an equal opportunity to seek, share and generate knowledge.Frontiers provides immediate and permanent online open access to all its publications, but this alone is not enough to realize our grand goals. Frontiers Journal SeriesThe Frontiers Journal Series is a multi-tier and interdisciplinary set of open-access, online journals, promising a paradigm shift from the current review, selection and dissemination processes in academic publishing.All Frontiers journals are driven by researchers for researchers; therefore, they constitute a service to the scholarly community.At the same time, the Frontiers Journal Series operates on a revolutionary invention, the tiered publishing system, initially addressing specific communities of scholars, and gradually climbing up to broader public understanding, thus serving the interests of the lay society, too. Dedication to QualityEach Frontiers article is a landmark of the highest quality, thanks to genuinely collaborative interactions between authors and review editors, who include some of the world's best academicians.Research must be certified by peers before entering a stream of knowledge that may eventually reach the public -and shape society; therefore, Frontiers only applies the most rigorous and unbiased reviews.Frontiers revolutionizes research publishing by freely delivering the most outstanding research, evaluated with no bias from both the academic and social point of view.By applying the most advanced information technologies, Frontiers is catapulting scholarly publishing into a new generation.